The role of concomitant chemoradiotherapy versus radiation alone in T1-3N0 HPV-positive and HPV-negative oropharyngeal squamous cell carcinoma. (July 2022) - Shiao, Jay C.; Holt, Douglas; Ladbury, Colton; Gao, Dexiang; Jones, Bernard; Karam, Sana D.; Amini, Arya
Highlights: Definitive RT is sufficient for T1-T2N0 OPSCC. Concurrent CRT is not recommended. T3N0 OPSCC should be treated with concurrent chemoradiation irrespective of p16 status. p16-positive T3N0 should be considered for clinical trials evaluating de-escalation. Abstract: Objective: To evaluate the role of curative intent concurrent chemoradiation (CCRT) vs radiation (RT) alone for T1-T3N0 HPV-positive and HPV-negative oropharyngeal squamous cell cancer (OPSCC). Methods: The NCDB was queried for patients diagnosed between 2010 and 2017 with cT1-3N0M0 OPSCC treated with definitive RT or CCRT. Univariable analysis (UVA) and multivariable analysis (MVA) Cox regression analysis was performed with OS as the endpoint. Propensity score matching (PSM) 1:1 was performed. Interaction test to assess heterogeneity of treatment effect. Results: A total of 2830 patients were queried. On MVA, CCRT was associated with improved OS for T3N0 tumors (HR 0.49; 95% CI 0.39–0.63) but not for T1N0 (HR 1.43; 95% CI 0.99–2.07) and T2N0 (HR 0.92; 95% CI 0.75–1.13). For T3 patients, CCRT improved OS for HPV-negative (HR 0.43; 95% CI 0.31–0.59) and HPV-positive tumors (HR 0.39; 95% CI 0.25–0.61). After PSM, CCRT was not statistically different to RT for patients with T1-2N0 HPV-negative tumors (HR 1.10; 95% CI 0.85–1.43; p = 0.48) and T1-2N0 HPV-positive tumors (HR 1.15; 95% CI 0.79–1.68; p = 0.45). After PSM, CCRT improved OS compared to RT alone for patients with T3N0 HPV-negative (HR 0.43; 95% CI 0.31–0.59; p < 0.01) and HPV-positive tumors (HR 0.39; 95 %CI 0.25–0.61; p < 0.01). Conclusions: CCRT is associated with improved OS in HPV-positive and HPV-negative T3N0 OPSCC. RT alone vs. CCRT demonstrated similar OS for T1-T2N0 OPSCC for both HPV negative and HPV positive tumors.